KERAJAAN SERIBU TAHUN DALAM WAHYU 20:1-6: SEBUAH ANALISIS TEMATIS DALAM KERANGKA TEOLOGI BIBLIKA - Silalahi, Binsar Pandapotan (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Revelation 20:1-6 is one of the central passages in New Testament eschatological discourse because it contains the only explicit mention of the thousand-year kingdom. Most previous studies have interpreted this passage based on specific eschatological systems, such as premillennialism or amillennialism, without exploring the internal narrative and thematic structure that progressively shapes the theological meaning of the text. This study offers a thematic approach within the framework of biblical theology to examine the connection between the binding of Satan, the first resurrection, and the co-reign with Christ as a single, coherent theological unity. Using qualitative methods and literature review, the analysis was conducted through three stages: structural description, thematic identification, and narrative-theological synthesis based on the Greek text (NA28). The results of the study show that Revelation 20:1-6 presents a narrative configuration that is literal and factual, which not only expresses symbolic hope but also affirms the participation of God's people in the fulfillment of the divine plan through Christ's concrete actions in the future as a response to a world marked by ethical crisis and historical disorientation.